3 - African Languages Policy in the Education of South Africa: 20 Years of Freedom or Subjugation? - Neo Lekgotla laga Ramoupi, (Journal of Higher Education in Africa, 2014)
This paper focuses on the indigenous African languages policy in educa- tion debates in post-apartheid South Africa, and provides a policy review of language in education in the past 20 years of liberation in the South Africa. The research problem is that the post-1994 governments of South Africa stated in the Constitution of the Republic of South Africa (1996) that indigenous official African languages must be in the curricula of the education system. But the findings reflect that this constitutional mandate has not been accomplished in the twenty years of South Africa’s liberation. Conclusions drawn are that the former two official languages used in the education policies of the apartheid South Africa, i.e. English and Afrikaans, have continued to be used in pretended implementation of indigenous of- ficial African languages in the curricula of education of a free South Africa.